2012
DOI: 10.1021/ol3011369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trifluoromethyl-Substituted Cyclopropanes via Sequential Kharasch–Dehalogenation Reactions

Abstract: A two-step process for the synthesis of trifluoromethyl-substituted cyclopropanes is described. Halothane, an anesthetic agent, is added to olefins in a ruthenium-catalyzed Kharasch reaction. The resulting 1,3-dihalides are converted into cyclopropanes by dehalogenation with magnesium. This procedure represents an alternative to metal-catalyzed cyclopropanations involving trifluoromethyl diazomethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…As the incorporation of the CF 3 group into cyclopropanes represents important structural modifications which can improve the bioactivity of the target molecules, the synthesis of CF 3 -cyclopropanes has received a great deal of attention from the synthetic community. Traditional approaches such as intramolecular cyclization of CF 3 -substrates suffer from tedious procedures to prepare the starting materials. , Recently, Baran found that trifluoro­methyl­cyclo­propyl sulfinate salt is a good reagent for a radical reaction to afford CF 3 -cyclopropanes . But only one position of the cyclopropyl ring is substituted.…”
mentioning
confidence: 99%
“…As the incorporation of the CF 3 group into cyclopropanes represents important structural modifications which can improve the bioactivity of the target molecules, the synthesis of CF 3 -cyclopropanes has received a great deal of attention from the synthetic community. Traditional approaches such as intramolecular cyclization of CF 3 -substrates suffer from tedious procedures to prepare the starting materials. , Recently, Baran found that trifluoro­methyl­cyclo­propyl sulfinate salt is a good reagent for a radical reaction to afford CF 3 -cyclopropanes . But only one position of the cyclopropyl ring is substituted.…”
mentioning
confidence: 99%
“…The group of Severin described a two-step procedure for the synthesis of CF 3 -cyclopropanes (Scheme 16). [49] CF 3 CHClBr could be easily reduced by a Ru complex to generate a CF 3 CHCl * radical. The first step is the radical addition of CF 3 CHCl * to a terminal alkene to give 17.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…In 2012, Severin and coworkers reported a sequential Kharasch dehalogenation–cyclization reaction for the synthesis of trifluoromethyl‐substituted cyclopropanes 73 a – f starting from 2‐bromo‐2‐chloro‐1,1,1‐trifluoroethane 72 (halothane) and styrene derivatives 71 a – f . Although the Kharasch reaction of halothane, promoted by Na 2 S 2 O 4 as a radical initiator, has already been developed with cyclic enol ethers, β‐pinene, and allyl benzene, the reaction with styrenes has not been reported.…”
Section: Trifluoromethyl‐substituted Cyclopropanesmentioning
confidence: 99%